Investigation of hydrogen recycling in long-duration discharges and its modification with a hot wall in the spherical tokamak QUEST. (26th October 2017) - Hanada, K.; Yoshida, N.; Honda, T.; Wang, Z.; Kuzmin, A.; Takagi, I.; Hirata, T.; Oya, Y.; Miyamoto, M.; Zushi, H.; Hasegawa, M.; Nakamura, K.; et al.
Abstract: Fully non-inductive plasma maintenance was achieved by a microwave of 8.2 GHz and 40 kW for more than 1 h 55 min with a well-controlled plasma-facing wall (PFW) temperature of 393 K, using a hot wall in the middle-sized spherical tokamak QUEST, until the discharge was finally terminated by the uncontrollability of the density. The PFW was composed of atmospheric plasma-sprayed tungsten and stainless steel. The hot wall plays an essential role in reducing the amount of wall-stored hydrogen and facilitates hydrogen recycling. The behaviour of fuel hydrogen in the PFW was investigated by monitoring the injection and evacuation of hydrogen into and from the plasma-producing vessel. A fuel particle balance equation based on the presence of a hydrogen transport barrier between the deposited layer and the substrate was applied to the long-duration discharges. It was found that the model could readily predict the observed behaviour in which a higher wall temperature likely gives rise to faster wall saturation.